Analysis and critique how to engage and write about anything - Armstrong, Dorsey, 1970-; Teaching Company (Chantilly, Va. : Teaching Co., 2011)
All writing--whether it's an essay, a personal letter, or a detailed business report--is at its most memorable when it's built on the fundamental and critical skills that transform yur words from good to great. The first lectures provides the first key to more engaging and effective writing: understanding literary genres and the ways their unique styles can shape and inform your own voice. The focus then shifts to the art of rhetoric and the ways it can help you adapt youir writing to a variety of situations. The final part is a step-by-step guide through the writing process in its four major stages: researching, first draft, edting and rewriting.
disc 1. Lectures 1-6. How to write about anything ; How to be an effective reader ; How literature can help ; Shaping your voice ; Knowing your reader ; The art of the essay : how to start -- disc 2. Lectures 7-12. How to organize an argument ; Supporting your argument ; Finishing strong ; The uses of poetry ; Poetic diction and syntax ; Drama : writing out loud. -- disc 3. Lectures 13-18. What you can learn from autobiography ; Writing and leadership ; The rules of rhetoric ; Invention and arrangement ; Ethos and pathos ; Finding what you need ; disc 4. Lecture 19-24. Using what you find ; Getting started : writing first drafts ; Editing : finding what's wrong ; Rewriting : fixing what's wrong ; Avoiding common errors in grammar and usage ; The power of words.
DVD (Region 1)
"Course No. 2133"--Disc label.
24 lectures (30 min. each) on four discs.
The accompanying course guidebook includes a glossary, biographical notes, and a bibliography.
Lecturer: Prof. Dorsey Armstrong, Purdue University.
Keywords: English language -- Rhetoric; Criticism; English language -- Writing; Report writing; Authorship; Nonfiction films; Educational films; Instructional films